Efficacies of Sodium Hypochlorite and Quaternary Ammonium Sanitizers for Reduction of Norovirus and Selected Bacteria during Ware-Washing Operations - Feliciano, Lizanel (Public Library of Science, 2012)
Cross-contamination of ready-to-eat (RTE) foods with pathogens on contaminated tableware and food preparation utensils is an important factor associated with foodborne illnesses. To prevent this, restaurants and food service establishments are required to achieve a minimum microbial reduction of 5 logs from these surfaces. This study evaluated the sanitization efficacies of ware-washing protocols (manual and mechanical) used in restaurants to clean tableware items. Ceramic plates, drinking glasses and stainless steel forks were used as the food contact surfaces. These were contaminated with cream cheese and reduced-fat milk inoculated with murine norovirus (MNV-1), Escherichia coli K-12 and Listeria innocua. The sanitizing solutions tested were sodium hypochlorite (chlorine), quaternary ammonium (QAC) and tap water (control). During the study, the survivability and response to the experimental conditions of the bacterial species was compared with that of MNV-1. The results showed that current ware-washing protocols used to remove bacteria from tableware items were not sufficient to achieve a 5 log reduction in MNV-1 titer. After washing, a maximum of 3 log reduction in the virus were obtained. It was concluded that MNV-1 appeared to be more resistant to both the washing process and the sanitizers when compared with E. coli K-12 and L. innocua.